Hedging Using Futures and Options Contracts in the Electricty Market - Azevedo, Filipe (2017)
Since the 80’s with the experience of Chile, the electric sector has suffered, in many counties, a process of deregulation and liberalization. In almost of the countries, that process originated the appearance of a Pool where the participants of the market trade the electrical energy on a basis of half-hour or one hour of the next day. However, like the traditional markets, the agents of electricity markets are now exposed to the volatility of market price, so far inexistent in those markets. In some countries, to face that problem and to turn the market more liquid have been introduced derivatives markets – futures and options, to negotiate products with underlying active the electrical energy. In this context, there is a need of decision-support tools that allow those agents to use derivatives markets with the objective of practicing the hedge and simultaneously increase their results. In this paper, we present a decision model that supports producers in the establishment of contracts with the objective to maximize the profit expected utility. The paper presents a group of examples of the use of this decision-support system.